Service-oriented computing – ICSOC 2016 workshops : ASOCA, ISyCC, BSCI, and Satellite Events, Banff, AB, Canada, October 10-13, 2016, Revised selected papers /: ASOCA, ISyCC, BSCI, and Satellite Events, Banff, AB, Canada, October 10-13, 2016, Revised selected papers. (2017) - Unknown
No abstract available